Inferência do valor de mercado de lotes urbanos. Estudo de caso : município de São Carlos (SP) - Ferraudo, Guilherme Moraes (Universidade Federal de São Carlos, 2008)
In this dissertation we present a regression modelling proposal for modelling the market prices of urban batches at São Carlos city (SP), over the year of 2005. Usual regression modelling and survival techniques, with left censoring, are considered. A simulation study exames the coverage probabilities the asymptotic confidence for the parameters of the considered modelling.
Keywords: Análise de sobrevivência; Modelos lineares (Estatística); Probabilidade de Cobertura; Loteamento; Localização residencial; Survival analysis with left censoring; Regression modelling; Coverage probability; Generic table of values; Urban intra-localization; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA